Sanctuary : a witch's tale. Season 1 [videorecording (DVD)] - Horsfield, Debbie, 1955- (Sundance Now, 2024)
In the idyllic English town of Sanctuary, where for hundreds of years witches have lived peacefully, the death of a teen rugby star exposes an undercurrent of suspicion.